2022
DOI: 10.3389/fsurg.2022.905372
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of NO and ET-1 Levels with Blood Pressure Changes in Hemodialysis Patients after Arteriovenous Fistula Surgery

Abstract: Hemodialysis (HD) is the most common renal replacement therapy for patients with end-stage renal disease (ESRD) and can significantly reduce mortality and improve the quality of life of patients. The occurrence of intradialytic hypotension and intradialytic hypertension are important risk factors for death and disability during dialysis in patients with ESRD, yet their etiology remains unclear, and some studies suggest that nitric oxide (NO) and endothelin-1 (ET-1) may play an important role in these hemodynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Teng et al [9] found that abnormally high ET-1 and the ET-1-to-nitric oxide (NO) ratio were characteristic findings in patients with IDHYPER. ET-1 levels were elevated in subjects with IDHYPER in the study of Li et al [10] and were also correlated with mean arterial pressure. Furthermore, in a study of 769 HD patients, baseline ET-1 levels were associated with both baseline systolic BP and the risk of developing IDHYPER (odds ratio: 1.21, 95% CI: 1.10–1.34) [11].…”
Section: Pathophysiologic Mechanisms Of Idhypermentioning
confidence: 94%
“…Teng et al [9] found that abnormally high ET-1 and the ET-1-to-nitric oxide (NO) ratio were characteristic findings in patients with IDHYPER. ET-1 levels were elevated in subjects with IDHYPER in the study of Li et al [10] and were also correlated with mean arterial pressure. Furthermore, in a study of 769 HD patients, baseline ET-1 levels were associated with both baseline systolic BP and the risk of developing IDHYPER (odds ratio: 1.21, 95% CI: 1.10–1.34) [11].…”
Section: Pathophysiologic Mechanisms Of Idhypermentioning
confidence: 94%